China's megatrends : the 8 pillars of a new society - Naisbitt, John, 1929-2021; Naisbitt, Doris (New York, NY : Harper Business, 2010)
Offers a perspective on the transformation that is reshaping China's economic, social, and political systems. This title includes information across China's provinces and cities. It argues that, while the US struggles to restore its position in the world, China is creating an entirely fresh social and economic model for a 21st-century.
Keywords: Economic forecasting -- China; Social prediction -- China; China -- Economic conditions -- 21st century; China -- Social conditions -- 21st century; China -- Condiciones económicas -- Siglo XXI; China -- Condiciones sociales -- Siglo XXI